Empowerment of PKK mothers through entrepreneurial skills education training - Nastia Nastia; Herman Lawelai; Hasimin Hasimin; Darni Darni (Community Empowerment, 2022)
The intention of this community service is to empower PKK mothers in Lasalimu District with entrepreneurial knowledge, skills in the sphere of goods/services production, and an entrepreneurial mentality. The lecture and discussion approach is used in this PKM activity. As a consequence of this program, there is an increase in participants' capacity about the knowledge of fundamental business skills, both individually and in groups, in an attempt to boost family economic income. This initiative also gives PKK mothers in Lasalimu District fresh ideas into how social media may help them run a business without having to invest a lot of money and have a vast network without being constrained by geography.